Context-Dependent Risk & Benefit Sensitivity Mediate Judgments About Cognitive Enhancement. Issue 1 (2nd January 2022) - Fernandez, Kiante; Hamilton, Roy; Cabrera, Laura; Medaglia, John Dominic
Abstract: Opinions about cognitive enhancement (CE) are context-dependent. Prior research has demonstrated that factors like peer pressure, the influence of authority figures, competition, moral relevance, familiarity with enhancement devices, expertise, and the domain of CE to be enhanced can influence opinions. The variability and malleability of patient, expert, and public attitudes toward CE is important to describe and predict because these attitudes can influence at-home, clinical, research, and regulatory decisions. If individual preferences vary, they could influence opinions about practices and regulations due to disagreements about the desirable levels of risks and benefits. The study of attitudes about CE would benefit from psychological theories that explain judgments. In particular, we suggest that variability in risk and benefit sensitivity could psychologically mediate judgments about CE in many contexts. Drawing from prospect theory, which originated in behavioral economics, it is likely that framing effects, shifted reference points, and the tendency to weigh losses (risks) more heavily than gains (benefits) predict decisions about CE. We suggest that public policy could benefit from a shared conceptual framework, such as prospect theory, that allows us to describe and predict real-world decisions about CE by patients, experts, and the public.